Enteritis cystica profunda with intestinal intussusception in an infant - Isadora de C. Trevizoli; Daniele A. Lira; Paulo M.S. Lassance; Heinrich B.K. Seidler; Elisa de Carvalho (Elsevier, 2018)
This publication reports enteritis cystica profunda (ECP) in the youngest patient described in the literature, being the fifth case that demonstrates an association between ECP and intestinal intussusception and the seventh case of ECP in children.A 30-day-old boy presented intense abdominal pain associated with digestive bleeding with "red currant jelly" stool. He had a history of bloody stool at 15 days old. Due to family history of atopy and normal physical examination, allergic proctocolitis was suspected and the patient temporarily improved after cow's milk and dairy products were eliminated from his mother's diet. Abdominal ultrasound confirmed the hypothesis of intestinal intussusception. During the surgical approach, ileoileal invagination was evident together with a polypoid tumor of the intestinal wall. Resection of the lesion and ileoileal anastomosis was performed. In the postoperative period, he presented intestinal adhesions, with the need of reoperation and, subsequently, dehiscence of the aponeurosis and intestinal perforation. The patient underwent operation with good recovery. He was discharged in good health and maintained satisfactory clinical progress.The histopathological study of the resected intestine (terminal ileum) revealed a lesion formed by cystic dilations with invasion to the submucosa and musculature of the intestinal wall, lined by intestinal epithelium cells and without nuclear atypia; these findings are compatible with ECP.